Impact of heat stress on prolactin-mediated ovarian JAK-STAT signaling in postpubertal gilts. (1st July 2022) - Roach, Crystal M; Bidne, Katie L; Romoser, Matthew R; Ross, Jason W; Baumgard, Lance H; Keating, Aileen F
Abstract: Heat stress (HS ) compromises almost every aspect of animal agriculture including reproduction. In pigs, this infecundity is referred to as seasonal infertility (SI ), a phenotype including ovarian dysfunction. In multiple species, HS-induced hyperprolactinemia has been described; hence, our study objectives were to characterize and compare HS effects on circulating prolactin (PRL ) and ovarian Janus kinase/signal transducer and activator of transcription (JAK-STAT ) signaling during the follicular (FOL ) or luteal (LUT ) phases of the estrous cycle in postpubertal gilts. Gilts were estrus synchronized using altrenogest and environmental treatments began immediately after altrenogest withdrawal. For the FOL study: postpubertal gilts were allocated to constant thermoneutral (TN ; n = 6; 20 ± 1.2 °C) or cyclical HS ( n = 6; 25 to 32 ± 1.2 °C) conditions for 5 d. In the LUT study: postpubertal gilts were assigned to either TN ( n = 7; 20 ± 2.6 °C) or cyclical HS ( n = 7; 32 to 35 ± 2.6 °C) conditions from 2 to 12 days postestrus (dpe ). Blood was collected by jugular venipuncture for PRL quantification on day 5 in the FOL and on day 0 and day 12 in the LUT gilts. Ovaries and corpora lutea (CL ) were obtained from euthanized FOL and LUT gilts on day 5 and day 12, respectively. Western blotting was performed to quantify prolactin receptor (PRLR ) and JAK/STAT pathway protein abundance. In the FOL phase, no difference ( P = 0.20) in circulating PRL between thermal groups was observed. There was no effect ( P ≥ 0.34) of HS on PRLR, signal transducer and activator of transcription 3 (STAT3 ), signal transducer and activator of transcription 5α (STAT5α ), and phosphorylated signal transducer and activator of transcription α/β tyrosine 694/699 (pSTAT5α/β Tyr694/699 ) abundance and Janus kinase 2 (JAK2 ), phosphorylated janus kinase 2 tyrosine 1007/1008 (pJAK2 Tyr1007/1008 ), STAT1, phosphorylated signal transducer and activator of transcription 1 tyrosine 701 (pSTAT1 Tyr701 ), phosphorylated signal transducer and activator of transcription 1 serine 727 (pSTAT1 Ser727 ), and phosphorylated signal transducer and activator of transcription 3 tyrosine 705 (pSTAT3 Tyr705 ) were undetectable in FOL gilt ovaries. Ovarian pSTAT5α/β Tyr694/699 abundance tended to moderately increase (4%; P = 0.07) in FOL gilts by HS. In the LUT phase, circulating PRL increased progressively from 2 to 12 dpe, but no thermal treatment-induced difference ( P = 0.37) was noted. There was no effect ( P ≥ 0.16) of HS on CL abundance of PRLR, pJAK2 Tyr1007/1008, JAK2, STAT1, pSTAT1 Tyr701, pSTAT1 Ser727, pSTAT3 Tyr705, STAT5α, or pSTAT5α/β Tyr694/699 . In LUT phase, CL STAT3 abundance was increased (11%; P < 0.03) by HS. There was no impact of HS ( P ≥ 0.76) on levels of pJAK2 Tyr1007/1008 and pSTAT5α/β Tyr694/699 in LUT gilts; however, the CL pSTAT3 Tyr705 :STAT3 ratio tended to be decreased ( P = 0.10) due to HS. These results indicate an HS-induced estrous cycle-stage-dependent effect on the ovarian JAK/STAT pathway, establishing a potential role for this signaling pathway as a potential contributor to SI. Lay Summary: Heat stress (HS) negatively affects reproduction in pigs, though the precise mechanisms are not understood. This study determined if HS impacts the JAK-STAT signaling pathway in the ovary during two stages of the estrous cycle: follicular and luteal. While circulating prolactin hormone level was unchanged, there were changes to some aspects of ovarian JAK-STAT signaling that could be involved in infertility induced in pigs during HS. Abstract : Heat stress causes hyperprolactinemia in several species. This study examined a role for prolactin-mediated ovarian and luteal JAK-STAT alterations during heat stress in the pig.